Foam Concrete: A State-of-the-Art and State-of-the-Practice Review. (26th March 2020) - Fu, Yanbin; Wang, Xiuling; Wang, Lixin; Li, Yunpeng
Abstract : Foam concrete (FC) has the potential of being an alternative to ordinary concrete, as it reduces dead loads on the structure and foundation, contributes to energy conservation, and lowers the cost of production and labor cost during the construction and transportation. The paper reports a state-of-the-art review of foam concrete in terms of its components, manufacturing and material properties like drying shrinkage, compressive strength, stability and pore structure, etc. In view of the significance of the FC in engineering construction, it also includes a state-of-the-practice review of foam concrete in tunnel and underground engineering. Some shortcomings and technical limitations as well as emerging direction for performance enhancement of FC are also discussed. Current review concludes that the long-term performance and enhancement-associated properties need to be deeply investigated. This study can help alleviate consumer concerns and further encourage the wider application of FC in civil engineering.